Students’ Perception: The Technology Integration into Project-Based Learning in Writing Class - Dewi, Kadek Intan Rustiana; Padmadewi, Ni Nyoman; Artini, Luh Putu (Universitas Pendidikan Ganesha, 2022)
Technology-assisted Project-based Learning is an innovative teaching strategy brought by the inevitability of information and communication technology. The present study examined the students' perception of technology integration into Project-based Learning in writing class. The study adopted an explanatory sequential mixed-method design. A total of 98 English students agreed to participate in the study. The data were collected through close-ended questionnaire forms and interviews to support the findings from the questionnaires. The data were analyzed by calculating the questionnaire responses using descriptive quantitative analysis and supporting them with a qualitative description and interpretation. The finding revealed that the students responded positively to technology-assisted Project-based Learning in their writing class. Seven items of the affective domain showed the students obtained positive experiences during the technology integration. Besides, six items of the cognitive domain also showed high percentages that indicated students' positive responses. Lastly, two items of the psychomotor domain showed that the technology encouraged them to be more active and enthusiastic. Therefore, this result implies that teachers and students should embrace technology integration to improve learning processes and outcomes.